Effective Width of the T-section Flange of Ribbed Slabs - F. S. Zamaliev (Железобетонные конструкции)
Ribbed ceilings in reinforced concrete, and more recently in steel-reinforced concrete and wood-concrete versions, occupy a significant place in the total volume of buildings and structures. An analysis of the regulatory and technical literature shows that in domestic and foreign sources, empirical dependencies are proposed for assigning the effective width of a T-section flange, which does not lead to economical and reliable design solutions.The purpose of the study is to determine the calculated effective width of a flange of a tee monolithic section or a composite section of a floor. Based on the analysis of the stress-strain state of a bent tee section, analytical ex-pressions are written and formulas are obtained for determining the design flange width.